Estimación de la capacidad de campo y punto de marchitez permanente por regresión lineal múltiple con la composición granulométrica del suelo en el Valle Chicama, La Libertad - Rodríguez Armas, Alan Percy (2009)
The present study is important were realize for obtain information on the hydraulic properties as from of the composition of soil texture agricultura! , this method of easy execution and as well economic, constitute the functions of pedotransfer an great alternative for determine these properties, useful of the programming of irrigations, anyone is the method of irrigation, irrigation by gravity oras pressure (sprinkling and dripping) and others uses edaphologys. This work were realize in the valley Chicama, by sixty- three representative points of twenty- two fields ofThe Company Agroindustrial Casa Grande S.A.A, point that were realize analyzed in the Laboratory of Agrohidrology of determine the Curves of Humidity Retention and of the texture Soil in the Laboratory Multifuntional of Soils of the FFCAA-UNT. With the information obtain of the hydric characteristics of the soils, the percentage of Humidity, Capacity ofField and Point ofPermanent Wilting and the percentage ofClay, Slime and Sand respectively to be realize the statistical analysis of multiple linear regression with software Excel for obtain new functions of pedotransfer. With the results of the analysis of variance for the coefficients of determination and correlation the results obtain validate as the equations of pedotransfer, respective y of capacity offield and Point ofPermanent Wilting being these highly significant. With the obtain results of the values estímate and measured, Capacity of Field and Point of Permanent Wilting, were determine the equations of prediction with an band of confidence to the 99,9% and almost totality ofthe measured values were meet within of the limits of confidence of the prediction equations, demonstrating itself that the prediction of values measured in field of Capacity of Field and Point of Permanent Wilting are highly significan! and were can possible determined indirectly by means ofthe values measured in the laboratory of the percentage of clay, slime and sand, the than agree for the determined for (RA WLS, et al,1982, PINEDA-VILORIA, et al,1997) and also (ZIMMERMANN, 2008). These results are of even application for the context of the alluvial Valle y of Chic ama for other contexts (Valleys ), is necessary to talk back these works following the same methodology.